Evaluating environmental education, citizen science, and stewardship through naturalist programs. Issue 6 (18th July 2016) - Merenlender, Adina M.; Crall, Alycia W.; Drill, Sabrina; Prysby, Michelle; Ballard, Heidi
Abstract: Amateur naturalists have played an important role in the study and conservation of nature since the 17th century. Today, naturalist groups make important contributions to bridge the gap between conservation science and practice around the world. We examined data from 2 regional naturalist programs to understand participant motivations, barriers, and perspectives as well as the actions they take to advance science, stewardship, and community engagement. These programs provide certification‐based natural history and conservation science training for adults that is followed by volunteer service in citizen science, education, and stewardship. Studies in California and Virginia include quantitative and qualitative evaluation data collected through pre‐ and postcourse surveys, interviews, and long‐term tracking of volunteer hours. Motivations of participants focused on learning about the local environment and plants and animals, connecting with nature, becoming certified, and spending time with people who have similar interests. Over half the participants surveyed were over 50 years old, two‐thirds were women, and a majority reported household incomes of over $50, 000 (60% in California, 85% in Virginia), and <20% of those surveyed in both states described themselves as nonwhite. Thus, these programs need to improve participation by a wider spectrum of the public. We interviewed younger and underrepresented adults to examine barriers to participation in citizen science. The primary barrier was lack of time due to the need to work and focus on career advancement. Survey data revealed that participants' ecological knowledge, scientific skills, and belief in their ability to address environmental issues increased after training. Documented conservation actions taken by the participants include invasive plant management, habitat restoration, and cleanups of natural areas and streams. Long‐term data from Virginia on volunteer hours dedicated to environmental citizen science show an increase from 14% in 2007 to 32% in 2014. In general, participants in the naturalist programs we examined increased their content knowledge about ecosystems, had greater confidence in conserving them, and continued to engage as citizen scientists after completing the program.